2008
DOI: 10.1371/journal.pntd.0000146
|View full text |Cite
|
Sign up to set email alerts
|

Helminthiasis and Hygiene Conditions of Schools in Ikenne, Ogun State, Nigeria

Abstract: BackgroundA study of the helminth infection status of primary-school children and the hygiene condition of schools in Ikenne Local Government Area of Ogun State, Nigeria was undertaken between November 2004 and February 2005 to help guide the development of a school-based health programme.Methods and FindingsThree primary schools were randomly selected: two government-owned schools (one urban and the other rural) and one urban private school. No rural private schools existed to survey. A total of 257 schoolchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
41
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 11 publications
9
41
1
4
Order By: Relevance
“…Similar fi ndings were reported from the study at Obio-Akpor Local Government Area [23] and in Ikenne [22]. They showed absent functional toilets in Public Schools.…”
Section: The Importance Of a Good And Functional School Healthsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar fi ndings were reported from the study at Obio-Akpor Local Government Area [23] and in Ikenne [22]. They showed absent functional toilets in Public Schools.…”
Section: The Importance Of a Good And Functional School Healthsupporting
confidence: 90%
“…This was similar to the study in Edo state where soap was present in 33% of the schools studied and 88% of them were Private Schools [14]. Others studies reported absence of hand washing soaps in the schools [18][19][20][21][22]. The study is a sharp contrast to that in the Schools in the Bloomberg Health District of London where 75-78% had soap and water for hand washing [24].…”
Section: The Importance Of a Good And Functional School Healthsupporting
confidence: 84%
See 1 more Smart Citation
“…Although, the findings of Ekpo et al (2008) in Ogun State, Nigeria have highlighted the relationship between helminthiasis and hygiene practices in school children [13]. There is an urgent need to provide evidence, if any, on the impact of current provision of community-based WASH resources on the transmission and control of STHs.…”
Section: Introductionmentioning
confidence: 99%
“…5 Many of these children are not without health challenges and the common health problems among them include malaria, respiratory tract infections, malnutrition, worm infestations, injuries due to accidents/falls and problems of adolescents such as teenage pregnancy, sexually transmitted diseases, drug and alcohol abuse. 6,7 It is universally recognized that the health of school children deserves special attention and in order to derive the maximum benefit from the educational programme, the child must be healthy physically, mentally and emotionally. 8 Research has shown that School Health Programmes can reduce the prevalence of health risk behaviors among young people and have a positive effect on academic performance.…”
Section: Introductionmentioning
confidence: 99%